Public perception of genetic engineering in Singapore. - Dudenhoeffer, Christine. (2008)
In this paper we research the public perception of genetic engineering in Singapore. So far, no study has examined the consumer attitude towards genetically engineered products in South East Asia. 2403 respondents, with a representative race and age profile, were surveyed in Singapore in 1999 with the aim of providing data to enable conclusions to be drawn on how these products could best be marketed in Singapore.